Stability of human telomere quadruplexes at high DNA concentrations - Kejnovská, Iva; Vorlíčková, Michaela; Brázdová, Marie; Sagi, Janos (Biopolymers, 2014)
For mimicking macromolecular crowding of DNA quadruplexes, various crowding agents have been used, typically PEG, with quadruplexes of micromolar strand concentrations. Thermal and thermodynamic stabilities of these quadruplexes increased with the concentration of the agents, the rise depended on the crowder used. A different phenomenon was observed, and is presented in this article, when the crowder was the quadruplex itself. With DNA strand concentrations ranging from 3 µM to 9 mM, the thermostability did not change up to ∼2 mM, above which it increased, indicating that the unfolding quadruplex units were not monomolecular above ∼2 mM. The results are explained by self-association of the G-quadruplexes above this concentration. The ΔG(°) 37 values, evaluated only below 2 mM, did not become more negative, as with the non-DNA crowders, instead, slightly increased. Folding topology changed from antiparallel to hybrid above 2 mM, and then to parallel quadruplexes at high, 6-9 mM strand concentrations. In this range, the concentration of the DNA phosphate anions approached the concentration of the K(+) counterions used. Volume exclusion is assumed to promote the topological changes of quadruplexes toward the parallel, and the decreased screening of anions could affect their stability.
Keywords: DNA concentration; Densitometry; elektroforéza v polyakrylamidovém gelu; folding topology; cirkulární dichroismus; thermal and thermodynamic stability; DNA; quadruplex; entropie; Spectrophotometry, Ultraviolet; mikroskopie atomárních sil; Entropy; Electrophoresis, Polyacrylamide Gel; G-kvadruplexy; Humans; Circular Dichroism; Microscopy, Atomic Force; denzitometrie; Telomere; telomery; G-Quadruplexes; spektrofotometrie ultrafialová; circular dichroism; lidé